Relación entre las formas de un verbo supletivo : el caso del gallego, comparado con el de otras lenguas iberorrománicas - Szijj, Ildikó (Acta Hispanica, 2011)
The verb 'go' (Spanish, Portuguese, Galician ir, Catalan anar) is a suppletive verb in theIberian romance languages. The roots and their distribution in the paradigm are similar in standardSpanish, Portuguese and Galician, but rather different in Catalan. There is a diachronic variatonand a synchronic difference between these languages in the 4th and 5th person of the present^ indicative mood. The variants can also be observed in dialects: according to the Galician UnguisticAtlas (Atlas lingüístico galego), the root can vary in the Galician linguistic territory in the previoustwo forms and in the 5th person of the imperative mood. These three forms within the paradigm arerelated in that thy are the "truly" arhygotonic forms in the three present tenses and they have thesame morphological structure.